Edukasi Dan Mengatasi Nyeri Bahu Dengan Terapi Latihan di Pos Lansia Banyuanyar Surakarta - Imro’atul Muflikha; Taufik Eko Susilo; Seliana Sinta Debi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Banyuanyar Village is located in Banjarsari District, Surakarta City. Banyuanyar Village is included in the status of urban areas and has a Puskesmas which plays an important role in public health. Patient visits at the Banyuanyar Health Center physiotherapy clinic for shoulder pain cases from 2022 were 25 patients while in 2023 they increased to 50 patients. The most common case is shoulder pain with the third highest case. Characterized by complaints of pain in the shoulder that hinder daily activities. The purpose of this program is to provide education and demonstrate exercises in cases of shoulder pain in order to reduce and prevent complaints. The method used was education in the form of counseling and distributing leaflets to the elderly at the Banyuanyar RW 03 elderly post. The results obtained from measuring the increase in understanding using the pre-test and post-test questionnaires were a significant increase in understanding regarding exercise with a pre-test average value of 10 and a post-test average value of 85.5